Melawan Stigma Diskriminatif: Strategi Pemberdayaan Penyandang Disabilitas di Desa Panggungharjo - Siregar, Nurul Aldha Mauliddina; Purbantara, Arif (UIN Sunan Kalijaga, Yogyakarta, Indonesia, 2020)
This article is an analysis of the powerless stigma of people with disabilities that still occurs in social life. The study was conducted to find out the process and method specifically carried out by the village government of Panggungharjo in initiating the presence of an environment that is inclusive of persons with disabilities. The study was conducted qualitatively through in-depth interview techniques, observation, and secondary data collection. As a result of the research shows that the village government of Panggungharjo can be changing the stigma of discrimination for people with disabilities more meaningful in their life. This acts as an empowerment strategy that can people with disabilities not only an object but also a subject of development programs. The people with disabilities were given the role of advancing village in the concern of artistic and cultural programs. The role creates people with disabilities to able independently in social life and accepted by village people. Therefore, the debate continues with the viewpoint of society that is the persons with disabilities identically stigma on an inability to work. This condition brings to the trouble of reaching their economic independence. Moreover, for the local community in rural areas, persons with disabilities are still often regarded as cursed creatures or carriers of disasters in the family which causes them to experience psychological disorders and difficulties in socializing. Hence, a draw of discrimination fend stigma it's needs of the strategy steps by the government village on sustainability.Artikel ini menganalisis stigma ketidakberdayaan penyandang disabilitas yang masih terjadi dalam kehidupan bermasyarakat. Penelitian ini juga dilakukan untuk mengetahui proses serta cara yang secara spesifik dilakukan pemerintah Desa Panggungharjo dalam menginisiasi hadirnya lingkungan yang inklusif bagi difabel. Penelitian dilakukan secara kualitatif melalui teknik wawancara, observasi, dan pengumpulan data sekunder. Hasil penelitian menunjukkan bahwa pemerintah Desa Panggungharjo mampu mengubah stigma diskriminatif bagi penyandang disabilitas kepada tindakan yang lebih bermakna. Tindakan ini sebagai strategi pemberdayaan untuk menjadikan penyandang disabilitas tak lagi sebagai obyek melainkan subyek pembangunan. Masyarakat penyandang disabilitas diberikan peran dalam memajukan desa dengan terlibat dalam program budaya dan kesenian. Peran ini menciptakan masyarakat penyandang disabilitas mampu mandiri untuk mencukupi kebutuhan hidup dan diterima oleh masyarakat desa. Namun perdebatan masih berlanjut tatkala cara pandang masyarakat yang kerap mengindentikkan penyandang disabilitas dengan ketidakmampuan untuk bekerja. Kondisi ini menyebabkan mereka sulit mencapai kemandirian secara ekonomi. Terlebih, untuk lingkungan masyarakat pedesaan, penyandang disabilitas masih sering dianggap sebagai kutukan dan aib keluarga. Hal ini menyebabkan mereka mengalami gangguan secara psikologis dan kesulitan untuk bersosialisasi. Untuk itu, tawaran menarik untuk menepis stigma diskriminatif tersebut membutuhkan langkah strategis pemerintah desa secara berkelanjutan.